Definição, dimensões e fatores moderadores do engajamento: validação de instrumentos de pesquisa multidimensionais - Kortz, Bruno José Viana (Universidade Federal de São Carlos, 2023)
The term 'engagement' initially conveys commitment between two parties, particularly in its origins, where 'engagement' represents the commitment between betrothed individuals at the moment of marriage. However, the concept of engagement is addressed in various fields of knowledge, such as psychology and applied social sciences, when referring to political and social engagement. In recent years, this concept has gained prominence among managers and academics, especially after its association with behaviors exhibited by social media users. However, its theoretical meaning and practical application are not yet well-established. Consequently, this research aims to analyze the meaning of engagement by identifying the moderating factors influencing its level across various dimensions in a business context. To achieve this objective, we conducted a systematic literature review and bibliometric analysis of 688 articles from the Scopus and Web of Science databases, aiming to comprehend the term in the context of business and its applicability. The findings revealed a lack of consensus regarding the theoretical definition, a scarcity of relevant empirical studies on its measurement, and primarily, the existence of distinct dimensions of engagement within the business context, particularly focusing on customer engagement, employee engagement, and organizational engagement. Subsequently, two research instruments were devised for customer and employee dimensions, alongside the development of an instrument based on theoretical review for the organizational dimension. These instruments underwent a four-stage validation process involving ten expert judges from the research field who are actively involved in professional practice. These experts contributed to the cultural and practical adaptations of the instruments for their application in the national context, utilizing the Content Validation Coefficient (CVC) for quantitative validation of the collected data. The validated instruments hold the potential to contribute to measuring the level of engagement across different organizational dimensions and empirically validating the concept within the national context. From an academic standpoint, the research provided a theoretical definition of engagement in the business context and proposed a new theoretical concept: engagement orientation. From a practical perspective, the research offered a definition and clarification of what engagement entails and how to strategically investigate it, aiming for superior organizational performance. Furthermore, the research opens numerous avenues for studying each dimension of engagement and its potential correlations. It also brings forth significant social contributions, as organizations, by understanding the benefits of engaged stakeholders, can strategically and practically address social and sustainable issues, ultimately aiming for a better perception of their performance
Definition, dimensions and moderating factors of engagement: validation of multidimensional research instruments
Keywords: Teoria do engajamento; Dimensões do engajamento; Orientação ao engajamento; Revisão Sistemática de Literatura; Coeficiente de Validação de Conteúdo; Engagement theory; Content Validation Coefficient; Systematic Literature Review; Engagement Orientation; Engagement dimensions; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS